"I think you are doing a bad job!" : The Effect of Blame Attribution by a Robot in Human-Robot Collaboration - van der Hoorn, Diede P.M.; Neerincx, Anouk; de Graaf, Maartje M.A. (2021 16th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2021)
Robots will increasingly collaborate with human partners necessitating research into how robots negotiate negative collaborative outcomes. This study investigates the effect of blame attribution on trust assessments in human-robot collaboration. Participants (n=60) collaboratively played a game with a humanoid robot in one of four conditions in a 2 (blame correctness: correct vs. incorrect) by 2 (blame target: human vs. robot) between-subjects experiment. Results show that people evaluate a robot more positively when it blames itself for collaborative failures, especially, it seems, in the case of incorrect self-blame. Our findings indicate a need to further research on effective communication strategies for robots that need to negotiate collaborative failures without compromising the trust relationships with its human partner. CCS CONCEPTS * Human-centered computing →Empirical studies in collaborative and social computing;* Computer systems organization →Robotics.